(3OjhGf SHW GHf GdJYGhjPjs - (3GHf GdJYGhjPj , CHh GdaJM eMeO Hf YHjOGddg Hf YHO Gddg, GHf GdJYGhjPj,J (B583 (3g` s
(3ChdgG (B:s
(3Chd eG ajg ef GdTYQ ef bUjOI jeOM HgG CejQ GdeDefjf GdfGUQ dOjf Gddg CHGGdYHGS CMeO YfO LdhSg aj GdNdGaI SfI (B575 s
(3BNQgG (B:s
(3MJi JQGgG dfG YbGdkG aj GdjO hGdQrLd hGddSGf s
(3CfLR GdfGSN eG CTGQ Hg GdTGYQ ef GdRjGOGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B278s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B114 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B766s
Keywords: (3GdCOHs